Oral Health Knowledge and Practice Behaviour among Secondary School Children in Shahzadpur Upazilla, Siraganj, Bangladesh. - Gazi Ikhtiar Ahmed; Farkhanda Mah Jebin; Md Ahsan Habib; Md Nahidul Islam; Shaila Zaman; Samiul Hasan Melar; Md Nurun Nabi Arafat (KYAMC Journal, 2023)
Background: A healthy oral cavity is of great significance for an individual’s overall health and well-being. Further, it enables an individual to masticate, speak and socialize without any active discomfort or embarrassment. Objectives: The study was conducted with the objective of revealing the condition of Healthy Oral Health Practice among a Selected Secondary School Children of Sirajganj District. Materials & Methods: This was a descriptive cross-sectional survey conducted during the month of April-June 2022. The target population for this study were the people residing in secondary school children of Shahjadpul upazila in the Sirajganj district. A convenience sampling technique was adopted. A total of 325 respondents were included in the study. Results: The age of study population ranged between 13 to 15 years with a mean age of 14 years. Data pertaining to the oral hygiene habits among the study population (n=325). The survey revealed that approximately 56.9% of the population studied, brushed their teeth once daily, while 38.5% respondents brushed twice a day. About knowledge towards general oral health, most of sample subjects were aware that sweets (89.8%) & smoking (65.5%) was not good for dental health. 85.6% of the respondents knew about the detrimental effect of paan/ tobacco respectively on oral health. About half the respondents were aware that maligned teeth could affect oral health. A variable proportion of respondents were aware of the adverse effects of various habits e.g., thumb sucking (29.2%) and nail biting (48.0%). Conclusions: This survey furnishes the background data to get insight into the status of awareness of secondary-level school students regarding oral health. KYAMC Journal Vol. 14, No. 02, July 2023: 64-68.